2017
DOI: 10.1155/2017/5356760
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Human Umbilical Cord Mesenchymal Stem Cells Relieve Inflammatory Bowel Disease in Mice

Abstract: Exosomes secreted by mesenchymal stem cells (MSCs) have shown repairing effects on several tissue injury diseases. In this study, we aimed to investigate the effects of exosomes released from human umbilical cord mesenchymal stem cells (hucMSCs) on the treatment of dextran sulfate sodium- (DSS-) induced inflammatory bowel disease (IBD) and to explore the underlying mechanism. We found that indocyanine green (ICG) labeled exosomes homed to colon tissues of IBD mice at 12 hours after injection. Exosomes signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(156 citation statements)
references
References 47 publications
8
138
0
Order By: Relevance
“…and MCP-1, whereas upregulated that of the anti-inflammatory M2 macrophage markers, Arg-1 and IL-10. These results are consistent with the findings of the studies conducted on animal model of IBD that have reported a M1 to M2 macrophage phenotype switching after treatment with extracts and exosomes from MSCs (Mao et al, 2017;Song et al, 2017). Several studies have proven that MSCs have the ability to inhibit cytotoxicity of NK cells and T cell proliferation via production of prostaglandin E2 (Németh et al, 2009), repression of differentiation of circulating T follicular helper cells by production of indoleamine 2,3-dioxygenease (François, Romieu-Mourez, Li, & Galipeau, 2012), stimulation of immunomodulatory cytokines synthesis, such as TGFβ1, IL-10, HGF, IL-1 receptors antagonist and TNF-stimulated gene 6 proteins (TSG-6), and induction of macrophage polarization toward anti-inflammatory M2 phenotype (Zheng, Ge, Qiu, Shu, & Xu, 2015).…”
Section: Coadministration Of Ascs and Sulfasalazine Downregulated Thesupporting
confidence: 93%
“…and MCP-1, whereas upregulated that of the anti-inflammatory M2 macrophage markers, Arg-1 and IL-10. These results are consistent with the findings of the studies conducted on animal model of IBD that have reported a M1 to M2 macrophage phenotype switching after treatment with extracts and exosomes from MSCs (Mao et al, 2017;Song et al, 2017). Several studies have proven that MSCs have the ability to inhibit cytotoxicity of NK cells and T cell proliferation via production of prostaglandin E2 (Németh et al, 2009), repression of differentiation of circulating T follicular helper cells by production of indoleamine 2,3-dioxygenease (François, Romieu-Mourez, Li, & Galipeau, 2012), stimulation of immunomodulatory cytokines synthesis, such as TGFβ1, IL-10, HGF, IL-1 receptors antagonist and TNF-stimulated gene 6 proteins (TSG-6), and induction of macrophage polarization toward anti-inflammatory M2 phenotype (Zheng, Ge, Qiu, Shu, & Xu, 2015).…”
Section: Coadministration Of Ascs and Sulfasalazine Downregulated Thesupporting
confidence: 93%
“…These results suggest that colonic macrophages are at least 1 source of the increased IL-10 and reinforce the notion that macrophage-derived IL-10 is a critical mediator of the anticolitic benefit of MSC-Exos. Nevertheless, macrophage-derived IL-7 may be involved in ameliorating murine experimental colitis when treated with exosomes from human umbilical cord MSCs (37). Therefore, we cannot exclude the possibility that additional factors after transfer of MSC-Exos in DSS-colitic mice may also play a role in protection from colitis because neutralization of IL-10 alone did not fully block the anticolitic effect of MSC-Exos.…”
Section: Discussionmentioning
confidence: 91%
“…Several recently published studies indicated that MSC-based alleviation of colitis was mainly relied on MSC-EV-induced suppression of colon macrophages [25][26][27][28] (Figure 1). Cao and colleagues showed that MSC-EVs significantly alleviated dextran sulphate sodium (DSS)-induced colitis in mice by inducing polarization of colon macrophages in immunosuppressive, M2 phenotype [25].…”
Section: Macrophages: the Main Cellular Targets Of Msc-derived Evs Inmentioning
confidence: 99%